Configuring Dementia; How Nursing Students Are Taught to Shape the Sociopolitical Role of Gerontechnologies - Bergschöld, Jenny Melind (Frontiers in Sociology, 2018)
This paper contributes to the discussion on the materiality of age and ageing in this special issue by presenting a case that illustrates how nursing students are trained to shape gerontechnologies in ways that have socio-political consequences for older adults with dementia who are ageing at home. Drawing on ethnographical fieldwork and grounded theory, I deliberately stage a dialogue between STS theory on technology, and relational approaches to the social study of dementia in an analysis of a lecture where master students in a university nursing programme learn about gerontechnology and dementia. I identify inability to purposively use technology, recalcitrance and attentiveness as three problematic behaviours that are described as typical for older adults with dementia who are ageing at home, and selection and placement of gerontechnologies as two ways in which the nursing students are taught to delimit this behaviour by material means. I show how selection and placement of gerontechnologies are means by which care professionals shape gerontechnologies in ways that can disempower older adults who are ageing at home, and I show how the educators draw on a biomedical understanding of dementia to accomplish a link between disempowering, and caring for older adults with dementia. I argue that care professionals practices of shaping gerontechnologies can be understood as empirical sites where care professionals exercise power over older adults with dementia who are ageing at home by socio-material means. I conclude that there is a continued need for studies of gerontechnologies that stage analytical dialogues between STS theory and understandings from other fields with longer traditions of studying processes of ageing, to further elucidate how gerontechnologies can matter to older adults and the experience of ageing